The Status of Female Garment Workers’ Health on STIs/HIV and the Role of Garment Factory Owners in Bangladesh - Mahmood, Shakeel (European Scientific Journal, ESJ, 2020)
The RMG (ready-made garment) sector is an export-oriented industry in Bangladesh. RMG has given Bangladesh and its women an immense image boost in South Asia and globally. This paper focuses on critically examining the personal understanding of health risk faced by female garment workers (FGWs), particularly their sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) experiences, and what needs to be done by the owners of the garment factories in Bangladesh to improve the health status of their FGWs. A systematic and comprehensive literature search was carried out, which was published between 1995 and 2020. It was revealed by several studies that health is an essential issue for garment employees. Garment factory owners violate the safety and security of the workplace and maintain inhumane working conditions. FGWs have been sexually assaulted by male co-workers as well as factory owners within the workplace. These FGWs, therefore, become susceptible and vulnerable to life-threatening diseases such as HIV and STIs. The literature shows that 43% garment owners believe that sexual harassment does not influence factories growth and development. To resolve health problems, all the parties such as FGWs, Garment factory owners, Bangladesh Garment Manufacturers and Exporters Association (BGMEA), researchers, and policymakers in Bangladesh have to work together to improve the health of women, especially on STIs and HIV. Above all, FGWs, including male partners and the owners of the factories, should be involved in preventive programmes concerning HIV/STIs and sexual harassment.